Method for improving stability of quantum dot optical film
By adding water-resistant agent to the quantum dispenser and stirring with acrylic resin and scattering particles to form a quantum dot optical film, the problem of poor stability of the quantum dot optical film in high temperature and high humidity environment is solved, and significant stability improvement and cost reduction are achieved.
Patent Information
- Application Number
- CN202510188225.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-29
AI Technical Summary
The existing quantum dot optical films have poor stability in high temperature and high humidity environments and are prone to fluorescence quenching, which limits its promotion in commercial applications.
During the preparation of quantum dispensing water, the anti-water agent is added to form a mixed liquid and stirred with acrylic resin and scattered particles. Then, the quantum dot solution is added and the quantum dot optical film is formed. After coating the upper and lower barrier films, UV curing is carried out to prepare a quantum dot optical film.
It significantly improves the stability of the quantum dot optical film in high temperature and high humidity environments, reduces the impact of water and oxygen on quantum dots, extends the service life of the optical film, reduces production costs, and is suitable for large-scale production.
Smart Images

Figure BDA0005279189170000071 
Figure BDA0005279189170000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of quantum dot optical films, and in particular relates to a method for improving the stability of quantum dot optical films. Background Art
[0002] As a new type of nanomaterial, colloidal quantum dots (QDs) have been widely used in many fields in recent years due to their unique optoelectronic properties, such as controllable emission wavelength, narrow bandwidth, and high quantum efficiency. In particular, colloidal quantum dots have shown great potential in the fields of biomarkers, optoelectronic devices, and information display. Among them, the application of quantum dots in the field of liquid crystal display (LCD) backlight is particularly successful. By mixing quantum dots with acrylic resin to make quantum dot glue and using coating technology to prepare it into an optical film, the quantum dot optical film can significantly improve the color performance and energy efficiency of LCD displays.
[0003] Traditional LCD display technology usually uses blue light LED as the light source, and converts part of the blue light into green light and red light through a light conversion film, which is then mixed with the remaining blue light to form white light to achieve full-color display. However, quantum dot materials face an important challenge in practical applications: their sensitivity to water and oxygen. When quantum dots are exposed to water and oxygen environments, fluorescence quenching is prone to occur, resulting in a decrease in the performance of the optical film. Especially in high temperature and high humidity environments (such as 85°C, 85% relative humidity), the stability of quantum dot optical films is poor, which seriously limits their promotion in commercial applications.
[0004] In order to improve the stability of quantum dot optical films, two main methods are currently used: modification of quantum dot materials and use of barrier films with high water and oxygen blocking rates. Quantum dot modification usually improves its water and oxygen resistance by coating the surface of quantum dots with a layer of silicon dioxide (SiO2). The mechanism of this method is that under alkaline conditions, the silicon source undergoes hydrolysis to generate silanols, which then undergoes a condensation reaction with the surface of the quantum dots to form a silicon dioxide protective layer. However, this method has some limitations: first, the treatment process is time-consuming and difficult to meet the needs of large-scale production; second, it is difficult to ensure the uniformity of different batches of quantum dots during the coating process, which will affect the overall performance of the optical film. Another method is to place a barrier film with a high water and oxygen blocking rate on the upper and lower sides of the quantum dot glue layer to reduce the penetration of water and oxygen into the quantum dots, thereby reducing the frequency of contact between the quantum dots and water and oxygen and ensuring their optical properties. However, barrier films with high water and oxygen blocking rates are expensive, resulting in a significant increase in production costs, which limits their widespread application in quantum dot optical films.
[0005] In summary, existing quantum dot optical film stability improvement solutions have problems such as long processing time, difficulty in ensuring uniformity, or high production costs. Therefore, it is urgent to develop a low-cost and stable technical solution to effectively improve the stability of quantum dot optical films in high temperature and high humidity environments and promote their further application in display technology. Summary of the invention
[0006] In view of the deficiencies of the prior art, the present invention provides a method for improving the stability of quantum dot optical films, which can effectively protect quantum dots and improve the stability of quantum dot optical films under high temperature and high humidity conditions.
[0007] The present invention is achieved through the following technical solutions:
[0008] A method for improving the stability of a quantum dot optical film comprises the following steps:
[0009] Step 1) adding scattering particles and water repellent into acrylic resin to form a mixed solution, and stirring;
[0010] Step 2) After sufficient stirring, the quantum dot solution is added to the mixed solution, and then further stirred to form a quantum dot glue;
[0011] Step 3) Apply quantum dot glue between the upper and lower barrier films, and obtain a quantum dot optical film by UV curing.
[0012] Preferably, in step 1), the mass ratio of the scattering particles to the acrylic resin is 1:(10-50); and the mass ratio of the water repellent to the acrylic resin is 1:(25-200).
[0013] Preferably, the scattering particles in step 1) are one or more of titanium dioxide and silicon dioxide.
[0014] Preferably, the water repellent in step 1) is one or more of methyl oleate, ethyl oleate and butyl oleate; preferably, the water repellent is butyl oleate.
[0015] Preferably, in step 2), the mass ratio of the quantum dot solution to the mixed solution is 1:(10-40).
[0016] Preferably, the quantum dot solution in step 2) comprises green fluorescent quantum dots and red fluorescent quantum dots, and the mass ratio of the green fluorescent quantum dots to the red fluorescent quantum dots is (1-4):1.
[0017] Preferably, the green fluorescent quantum dots and the red fluorescent quantum dots are CdSe core quantum dots or InP core quantum dots, which emit green fluorescence and red fluorescence respectively under blue light conditions, the wavelength range of the green fluorescence is 520-540 nm, and the wavelength range of the red fluorescence is 620-640 nm.
[0018] Preferably, in step 1) and step 2), the stirring speed is 500-2000 rpm / min, and the stirring time is 30-90 min.
[0019] Preferably, the structure of the upper and lower barrier films in step 3) is a barrier layer plus a PET substrate, with a thickness of 100 μm and a water and oxygen barrier rate of less than 10 -1 g / m 2 / day.
[0020] Preferably, in step 3), the thickness of the quantum dot optical film obtained by UV curing is 300-350 μm.
[0021] The beneficial effects of the present invention are as follows:
[0022] The present invention effectively reduces the influence of water and oxygen on quantum dots by adding a water repellent in the process of preparing quantum dot glue by mixing quantum dots with acrylic resin, thereby significantly improving the stability of quantum dot optical film in high temperature and high humidity (85°C, 85% RH) environment. First, the present invention does not need to perform complex surface modification treatment on quantum dot materials, nor does it need to use high-cost high water and oxygen barrier films. It only needs to add a water repellent in the preparation process of quantum dot glue, which is simple in process, easy to implement, and suitable for large-scale production. Secondly, compared with methods such as coating the surface of quantum dots with silicon dioxide or using high water and oxygen barrier films, the water repellent used in the present invention has a lower cost and no additional equipment investment, which significantly reduces the production cost and has higher economic benefits. In addition, by adding a water repellent, the stability of the quantum dot optical film in a high temperature and high humidity environment is significantly improved, which can effectively inhibit the fluorescence quenching phenomenon of quantum dots, extend the service life of the optical film, and meet the needs of commercial applications. The method of the present invention has a simple process, low cost, and low requirements for production equipment and environment, and can quickly achieve large-scale mass production, and has broad application prospects. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below with reference to specific embodiments.
[0024] Unless otherwise specified, the technical means used in the following examples are all conventional means well known to those skilled in the art, and the experimental methods without specifying the specific conditions are all conventional methods in the art.
[0025] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0026] A method for improving the stability of a quantum dot optical film, comprising the following steps:
[0027] (1) Add scattering particles and water repellent to acrylic resin to form a mixed solution, and stir at 500 to 2000 rpm / min for 30 to 90 minutes.
[0028] The mass ratio of the scattering particles to the acrylic resin can be 1:10, 1:20, or 1:50. The scattering particles are one or more of titanium dioxide and silicon dioxide. The scattering particles mainly scatter light, which can improve the luminous efficiency of quantum dots in the film and enhance the brightness of the quantum dot optical film.
[0029] The mass ratio of the water repellent to the acrylic resin can be 1:25, 1:50, 1:100, 1:200. The water repellent is one or more of methyl oleate, ethyl oleate, and butyl oleate. The water repellent is preferably butyl oleate. The mechanism is that ethyl oleate will undergo a hydrolysis reaction when it meets water under the action of an acid catalyst to generate a mixture of oleic acid, ethanol, etc., forming a protective film to effectively protect the quantum dots.
[0030] The acrylic resin is a light-curing resin, which undergoes a polymerization reaction under ultraviolet light to cure the quantum dot glue.
[0031] (2) After being fully stirred, the quantum dot solution is added to the mixed solution, and then fully stirred at 500 to 2000 rpm / min for 30 to 90 minutes to form quantum dot glue.
[0032] The mass ratio of the quantum dot solution to the mixed solution can be 1:10, 1:20, 1:30, or 1:40. The quantum dot solution includes green fluorescent quantum dots and red fluorescent quantum dots. The mass ratio of the green fluorescent quantum dots to the red fluorescent quantum dots can be 1:1, 2:1, 3:1, or 4:1. The green fluorescent quantum dots and the red fluorescent quantum dots are CdSe core quantum dots or InP core quantum dots, which emit green fluorescence and red fluorescence respectively under blue light conditions. The wavelength range of the green fluorescence is 520 to 540 nm, and the wavelength range of the red fluorescence is 620 to 640 nm. Quantum dots with different fluorescence wavelengths can be selected for combined use according to color point requirements.
[0033] (3) Applying quantum dot glue between the upper and lower barrier films, and then curing with UV to obtain a quantum dot optical film.
[0034] The structure of the upper and lower barrier films is a barrier layer plus a PET substrate, with a thickness of 100 μm and a water and oxygen barrier rate of less than 10 -1 g / m 2 / day, the thickness of the quantum dot optical film obtained by UV curing is 300-350μm.
[0035] (4) Cut the quantum dot optical film into a size of 21 cm × 21 cm, place it in a blue light module, and use a white point meter to test its initial optical data. The initial optical data are the color coordinate x, color coordinate y, and brightness L. Then, place the quantum dot optical film in a high temperature and high humidity box at 85°C and 85% RH for 1000 hours to test the changes in its optical data.
[0036] Example 1
[0037] A method for improving the stability of a quantum dot optical film, comprising the following steps:
[0038] (1) 50 g of titanium dioxide, 10 g of water repellent methyl oleate and 1000 g of acrylic resin were mixed to form a mixture, which was stirred at 1000 rpm / min for 60 min.
[0039] (2) After the mixed solution is fully stirred, 5 g of green CdSe quantum dot solution and 5 g of red CdSe quantum dot solution are added, and stirring is continued at 1000 rpm / min for 60 min to form quantum dot glue.
[0040] (3) Apply the stirred quantum dot glue on the upper and lower barrier films (water and oxygen barrier rate is less than 10 -1 g / m 2 / day), and a quantum dot optical film was obtained by UV curing.
[0041] (4) Cut the quantum dot optical film into a size of 21 cm × 21 cm, place it in a blue light module, and use a white point meter to test its initial optical data. The initial optical data are the color coordinate x, color coordinate y, and brightness L. Then, place the quantum dot optical film in a high temperature and high humidity box at 85°C and 85% RH for 1000 hours to test the changes in its optical data.
[0042] The quantum dot optical film prepared in this embodiment has a thickness of 100 μm and a total thickness of 300 μm. After being stored in a high temperature and high humidity box at 85°C and 85% RH for 1000 h, the color coordinate x decreases by 2.9‰, the color coordinate y decreases by 11.3‰, and the brightness L decreases by 14.2%.
[0043] Example 2
[0044] A method for improving the stability of a quantum dot optical film, comprising the following steps:
[0045] (1) 50 g of titanium dioxide, 10 g of water repellent ethyl oleate and 1000 g of acrylic resin were mixed to form a mixture, which was stirred at 1000 rpm / min for 60 min.
[0046] (2) After the mixed solution is fully stirred, 5 g of green CdSe quantum dot solution and 5 g of red CdSe quantum dot solution are added, and stirring is continued at 1000 rpm / min for 60 min to form quantum dot glue.
[0047] (3) Apply the stirred quantum dot glue on the upper and lower barrier films (water and oxygen barrier rate is less than 10 -1 g / m 2 / day), and a quantum dot optical film was obtained by UV curing.
[0048] (4) Cut the quantum dot optical film into a size of 21 cm × 21 cm, place it in a blue light module, and use a white point meter to test its initial optical data. The initial optical data are the color coordinate x, color coordinate y, and brightness L. Then, place the quantum dot optical film in a high temperature and high humidity box at 85°C and 85% RH for 1000 hours to test the changes in its optical data.
[0049] The quantum dot optical film prepared in this embodiment has a thickness of 100 μm and a total thickness of 300 μm. After being stored in a high temperature and high humidity box at 85°C and 85% RH for 1000 h, the color coordinate x decreases by 3.2‰, the color coordinate y decreases by 10.6‰, and the brightness L decreases by 13.8%.
[0050] Example 3
[0051] A method for improving the stability of a quantum dot optical film, comprising the following steps:
[0052] (1) 50 g of titanium dioxide, 40 g of water repellent ethyl oleate and 1000 g of acrylic resin were mixed to form a mixture, which was stirred at 1000 rpm / min for 60 min.
[0053] (2) After the mixed solution is fully stirred, 5 g of green CdSe quantum dot solution and 5 g of red CdSe quantum dot solution are added, and stirring is continued at 1000 rpm / min for 60 min to form quantum dot glue.
[0054] (3) Apply the stirred quantum dot glue on the upper and lower barrier films (water and oxygen barrier rate is less than 10 -1 g / m 2 / day), and a quantum dot optical film was obtained by UV curing.
[0055] (4) Cut the quantum dot optical film into a size of 21 cm × 21 cm, place it in a blue light module, and use a white point meter to test its initial optical data. The initial optical data are the color coordinate x, color coordinate y, and brightness L. Then, place the quantum dot optical film in a high temperature and high humidity box at 85°C and 85% RH for 1000 hours to test the changes in its optical data.
[0056] The quantum dot optical film prepared in this embodiment has a thickness of 100 μm and a total thickness of 300 μm. After being stored in a high temperature and high humidity box at 85°C and 85% RH for 1000 h, the color coordinate x decreases by 2.5‰, the color coordinate y decreases by 8.4‰, and the brightness L decreases by 10.8%.
[0057] Example 4
[0058] A method for improving the stability of a quantum dot optical film, comprising the following steps:
[0059] (1) 50 g of titanium dioxide, 10 g of water repellent butyl oleate and 1000 g of acrylic resin were mixed to form a mixture, and stirred at 1000 rpm / min for 60 min.
[0060] (2) After the mixed solution is fully stirred, 5 g of green CdSe quantum dot solution and 5 g of red CdSe quantum dot solution are added, and stirring is continued at 1000 rpm / min for 60 min to form quantum dot glue.
[0061] (3) Apply the stirred quantum dot glue on the upper and lower barrier films (water and oxygen barrier rate is less than 10 -1 g / m 2 / day), and a quantum dot optical film was obtained by UV curing.
[0062] (4) Cut the quantum dot optical film into a size of 21 cm × 21 cm, place it in a blue light module, and use a white point meter to test its initial optical data. The initial optical data are the color coordinate x, color coordinate y, and brightness L. Then, place the quantum dot optical film in a high temperature and high humidity box at 85°C and 85% RH for 1000 hours to test the changes in its optical data.
[0063] The quantum dot optical film prepared in this embodiment has a thickness of 100 μm and a total thickness of 300 μm. After being stored in a high temperature and high humidity box at 85°C and 85% RH for 1000 h, the color coordinate x decreases by 2.7‰, the color coordinate y decreases by 9.2‰, and the brightness L decreases by 11.2%.
[0064] Example 5
[0065] A method for improving the stability of a quantum dot optical film, comprising the following steps:
[0066] (1) 50 g of titanium dioxide, 40 g of water repellent butyl oleate and 1000 g of acrylic resin were mixed to form a mixture, and stirred at 1000 rpm / min for 60 min.
[0067] (2) After the mixed solution is fully stirred, 5 g of green CdSe quantum dot solution and 5 g of red CdSe quantum dot solution are added, and stirring is continued at 1000 rpm / min for 60 min to form quantum dot glue.
[0068] (3) Apply the stirred quantum dot glue on the upper and lower barrier films (water and oxygen barrier rate is less than 10 -1 g / m 2 / day), and a quantum dot optical film was obtained by UV curing.
[0069] (4) Cut the quantum dot optical film into a size of 21 cm × 21 cm, place it in a blue light module, and use a white point meter to test its initial optical data. The initial optical data are the color coordinate x, color coordinate y, and brightness L. Then, place the quantum dot optical film in a high temperature and high humidity box at 85°C and 85% RH for 1000 hours to test the changes in its optical data.
[0070] The quantum dot optical film prepared in this embodiment has a thickness of 100 μm and a total thickness of 300 μm. After being stored in a high temperature and high humidity box at 85°C and 85% RH for 1000 h, the color coordinate x decreases by 1.8‰, the color coordinate y decreases by 6.3‰, and the brightness L decreases by 8.1%.
[0071] Comparative Example 1
[0072] A method for preparing a quantum dot optical film, the specific steps are as follows:
[0073] (1) 50 g of titanium dioxide and 1000 g of acrylic resin were mixed to form a mixture, and the mixture was stirred at 1000 rpm / min for 60 min.
[0074] (2) After the mixed solution is fully stirred, 5 g of green CdSe quantum dot solution and 5 g of red CdSe quantum dot solution are added, and stirring is continued at 1000 rpm / min for 60 min to form quantum dot glue.
[0075] (3) Apply the stirred quantum dot glue on the upper and lower barrier films (water and oxygen barrier rate is less than 10 -1 g / m 2 / day), and a quantum dot optical film was obtained by UV curing.
[0076] (4) Cut the quantum dot optical film into a size of 21 cm × 21 cm, place it in a blue light module, and use a white point meter to test its initial optical data. The initial optical data are the color coordinate x, color coordinate y, and brightness L. Then, place the quantum dot optical film in a high temperature and high humidity box at 85°C and 85% RH for 1000 hours to test the changes in its optical data.
[0077] The quantum dot optical film prepared in this comparative example is a comparative sample without adding a water repellent, with a glue layer thickness of 100 μm and a total thickness of 300 μm. After being stored in a high temperature and high humidity box at 85°C and 85% RH for 1000 hours, the color coordinate x decreased by 7.4‰, the color coordinate y decreased by 13.5‰, and the brightness L decreased by 16.3%.
[0078] Test Example 1
[0079] The changes in optical data of the quantum dot optical films prepared in Comparative Example 1 and Examples 1-5 are summarized in Table 1 below.
[0080] Table 1 Summary of optical data changes
[0081]
[0082]
[0083] In Table 1: △x is the value of the color coordinate x after 1000 hours of high temperature and high humidity storage minus the initial color coordinate x; △y is the value of the color coordinate y after 1000 hours of high temperature and high humidity storage minus the initial color coordinate y; △L is the difference in brightness before and after high temperature and high humidity storage divided by the initial brightness value.
[0084] According to the experimental data in Table 1, the quantum dot optical film (Examples 1-5) prepared by adding a water repellent to the quantum dot glue of the present invention, after being stored for 1000 hours under high temperature and high humidity (85°C, 85% RH), has a significantly lower attenuation rate of color coordinates and brightness than the comparative example 1 without adding a water repellent. The specific analysis is as follows:
[0085] 1. Significantly improved color coordinate stability
[0086] Color coordinate x decay rate: The decay rates of Examples 1-5 range from 1.8‰ to 3.2‰, while the decay rate of Comparative Example 1 is 7.4‰. Among them, the color coordinate x decay rate of Example 5 (adding 4% water repellent butyl oleate) is the lowest, only 1.8‰, which is 75.7% lower than that of Comparative Example 1.
[0087] Color coordinate y decay rate: The decay rates of Examples 1-5 range from 6.3‰ to 11.3‰, while the decay rate of Comparative Example 1 is 13.5‰. The color coordinate y decay rate of Example 5 is the lowest, at 6.3‰, which is 53.3% lower than that of Comparative Example 1.
[0088] The above data show that the present invention significantly reduces the attenuation rate of the color coordinates of the quantum dot optical film in a high temperature and high humidity environment by adding a water repellent, thereby effectively improving the color stability.
[0089] 2. Brightness attenuation rate is significantly reduced
[0090] Brightness decay rate: The decay rates of Examples 1-5 range from 8.1% to 14.2%, while the decay rate of Comparative Example 1 is 16.3%. The brightness decay rate of Example 5 is the lowest, at 8.1%, which is 50.3% lower than that of Comparative Example 1.
[0091] This indicates that the present invention can effectively suppress the brightness attenuation of the quantum dot optical film in a high temperature and high humidity environment by adding a water repellent, thereby significantly improving the brightness stability of the optical film.
[0092] 3. Optimization effect of water repellent addition
[0093] Example 5 (adding 4% water repellent butyl oleate) performed best among all the examples, and its color coordinate x, y attenuation rate and brightness attenuation rate were the lowest, indicating that adding an appropriate amount of water repellent can maximize the stability of the quantum dot optical film.
[0094] 4. Comprehensive performance advantages
[0095] Compared with the prior art (Comparative Example 1), the present invention not only significantly reduces the attenuation rate of color coordinates and brightness by adding a water repellent, but also avoids complex quantum dot surface modification treatment or the use of high-cost high water and oxygen barrier films, and has the advantages of simple operation and low cost.
[0096] In summary, the present invention significantly improves the stability of quantum dot optical film in high temperature and high humidity environment by adding water repellent to quantum dot glue, which is specifically manifested in the significant reduction of color coordinates and brightness attenuation rate. Compared with the prior art, the present invention has the characteristics of simple operation, low cost and superior performance, and provides reliable technical support for the large-scale commercial application of quantum dot optical film.
[0097] The embodiments described above are only some embodiments of the present invention, rather than all embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. The scope of protection of the present invention shall be subject to the scope required by the claims. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work shall fall within the scope of protection of the present invention.
Claims
1. A method for improving the stability of a quantum dot optical film, characterized in that: The following steps are involved: Step 1) adding scattering particles and water repellent to acrylic resin to form a mixed solution, and stirring; Step 2) adding quantum dot solution to the mixed solution after sufficient stirring, and further sufficient stirring to form quantum dot glue; Step 3) Apply quantum dot glue between the upper and lower barrier films, and obtain a quantum dot optical film by UV curing.
2. A method for improving the stability of a quantum dot optical film according to claim 1, characterized in that: In step 1), the mass ratio of the scattering particles to the acrylic resin is 1:(10-50); the mass ratio of the water repellent to the acrylic resin is 1:(25-200).
3. A method for improving the stability of a quantum dot optical film according to claim 1, characterized in that: Step 1) The scattering particles are one or more of titanium dioxide and silicon dioxide.
4. The method for improving the stability of a quantum dot optical film according to claim 1, characterized in that: Step 1) The water repellent is one or more of methyl oleate, ethyl oleate, and butyl oleate; preferably, the water repellent is butyl oleate.
5. The method for improving the stability of a quantum dot optical film according to claim 1, characterized in that: Step 2) The mass ratio of the quantum dot solution to the mixed solution is 1:(10-40).
6. The method for improving the stability of a quantum dot optical film according to claim 1, characterized in that: Step 2) The quantum dot solution comprises green fluorescent quantum dots and red fluorescent quantum dots, and the mass ratio of the green fluorescent quantum dots to the red fluorescent quantum dots is (1-4):
1.
7. A method for improving the stability of a quantum dot optical film according to claim 6, characterized in that: The green fluorescent quantum dots and the red fluorescent quantum dots are CdSe core quantum dots or InP core quantum dots, which emit green fluorescence and red fluorescence respectively under blue light conditions. The wavelength range of the green fluorescence is 520-540nm, and the wavelength range of the red fluorescence is 620-640nm.
8. The method for improving the stability of a quantum dot optical film according to claim 1, characterized in that: In the step 1) and the step 2), the stirring speed is 500 to 2000 rpm / min, and the stirring time is 30 to 90 min.
9. The method for improving the stability of a quantum dot optical film according to claim 1, characterized in that: Step 3) The structure of the upper and lower barrier films is a barrier layer plus a PET substrate, with a thickness of 100 μm and a water and oxygen barrier rate of less than 10 -1 g / m 2 / day.
10. The method for improving the stability of a quantum dot optical film according to claim 1, characterized in that: Step 3) The thickness of the quantum dot optical film obtained by UV curing is 300-350 μm.
Citation Information
Cited By
Quantum dot ink with Z constant, Oh constant and We number cooperatively regulated and controlled and use method
CN121160142A